Analysis On Motivation In Learning English Among Pesantren Students And Its Correlation With English Language Proficiency: Analisis Motivasi Belajar Bahasa Inggris Di Kalangan Siswa Pesantren Dan Hubungannya Dengan Kemahiran Bahasa Inggris - Muhammad Zuhri Fakhruddin (Universitas Muhammadiyah Sidoarjo, 2021)
This quantitative descriptive research investigates correlation between English learning motivation among Pesantren students and their English language proficiency. Pesantren community is a unique environment to learn foreign language combining the process of nurturing Islamic values and discipline. 25 students of X grade from IPS (Social) major are involved in this study. A questionnaire measuring type of motivation and its value is used to collect data related to the motivation, while the English proficiency is measured through School based examination score and independent English language proficiency designed by the researcher. Analysis on the collected data is done through SPSS version 26. The finding revealed that there are four types of motivation among Pesantren students in learning English, those are: [1] Instrumental; [2] Integrative; [3] Extrinsic; and [4] Intrinsic. Each of these type has been proven to have a significance correlation with students English language proficiency. Thus it strengthen the previous theory stating that motivation plays significant role in learning. The most dominant type of motivation among Pesantren students is instrumental motivation.